Cumplimiento Tributario en la Cooperativa de Ahorro y Crédito Indígenas Galápagos, Matriz Santa Cruz Provincia de Galápagos en el período 2023. - Anancolla Masaquiza, Tannya Maribel (2026)
This research delves into the heart of the Galapagos Indigenous Savings and Credit Cooperative to understand and strengthen its commitment to fulfilling its tax obligations during 2023. In the dynamic economic and social landscape of the Galapagos Islands, properly complying with tax obligations is not only a legal requirement but also a pillar of trust, transparency, and sustainability for the cooperative, which serves a vital community. However, areas for improvement were identified stemming from internal management, such as potential staff errors and the need to formalize processes, which could lead to observations from the Internal Revenue Service (SRI). The central objective of this work was to determine the cooperative's actual level of tax compliance as required by the SRI. To achieve this, a qualitative and documentary methodology was used, with a descriptive and explanatory approach. The research was based on a thorough review of internal documentation, complemented by key techniques such as observation and an interview with the entity's accountant. The results showed that tax compliance is intrinsically linked to the quality of internal management. Inconsistencies were detected in tax returns and supporting documentation, primarily stemming from the lack of a clear policies and procedures manual and operational errors by staff, highlighting the risk of penalties and the impact on the entity's profitability. It is concluded that strengthening internal management and providing ongoing training are crucial for successful tax compliance. Therefore, practical recommendations are proposed to formalize processes and establish control measures, ensuring that the Galápagos Indigenous Savings and Credit Cooperative continues to operate with transparency, credibility, and long-term financial health, consolidating its position as an engine of development for the Galápagos Islands.